Multimedia Interaktif Bagi Siswa Berkebutuhan Khusus - Mukhammad Luqman Hakim (Al-Aulad: Journal of Islamic Primary Education, 2020)
ABSTRACTThe aim of this research is to apply interactive multimedia to students special needs. The use of interactive multimedia in the learning of Islamic Religious Education to provide different learning experiences for students special needs. The material included in interactive multimedia is “Mengenal Malaikat ALLAH SWT”. This research method uses a qualitative descriptive approach. This approach is intended to record the use of media in the learning of Islamic Religious Education at SLB Nurul Ikhsan Ngadiluwih which is conducted on 10 students, Islamic subject teachers and Principals who are the subjects. Indicators of the use of instructional media include planning, implementing and evaluating learning. As a qualitative descriptive study, the data collection method was carried out using interviews and observations. From this study found several things namely students are more motivated in learning, this is because the appearance of an interesting media and is equipped with an animation about the explanation of the material; students can learn anywhere and anytime because learning media is portable; the teacher gets ease in delivering subject matter.Keyword: Interactive multimedia, students special needs, mentally disabled.  ABSTRAKTujuan dari penelitian ini adalah untuk menerapkan multimedia interaktif kepada siswa berkebuthan khusus. Penggunaan multimedia interaktif dalam pembelajaran Pendidiakan Agama Islam untuk memberikan pengalaman belajar berbeda kepada siswa luar biasa. Materi yang dimasukkan dalam multimedia interaktif adalah materi Mengenal Malaikat ALLAH SWT. Metode penelitian ini menggunakan pendekatan deskriptif kualitatif. Pendekatan ini dimaksudkan untuk merekam pemanfaatan media dalam pembelajaran Pendidikan Agama Islam di SLB Nurul Ikhsan Ngadiluwih yang dilakukan kepada 10 siswa, guru mata pelajaran Pendidikan Agama Islam dan Kepala Sekolah yang menjadi subyeknya. Indikator pemanfaatan media pembelajaran meliputi perencanaan, pelaksanaan dan penilaian pembelajaran. Sebagai penelitian deskriptif kualitatif, metode pengumpulan data dilakukan dengan menggunakan, wawancara dan observasi. Dari penelitian ini ditemukan beberapa hal yaitu Siswa lebih termotivasi dalam beajar, hal ini dikarenakan tampilan media yang menarik dan dilengkapi dengan animasi tentang penjelasan materi; siswa bisa belajar dimana saja dan kapan saja karena media pembelajaran bersifat portable; guru mendapatkan kemudahan dalam penyampaian materi pelajaran.Kata kunci: Multimedia interaktif, siswa berkebutuhan khusus, tunagrahita.